Glistenings 9 years after phacoemulsification in hydrophobic and hydrophilic acrylic intraocular lenses. Issue 6 (June 2015) - Chang, Anthony; Kugelberg, Maria
Abstract : Purpose : To compare the development of glistenings after implantation of a hydrophobic acrylic intraocular lens (IOL) (AcrySof SA60AT) and a hydrophilic IOL (BL27) and evaluate the effect on corrected distance visual acuity (CDVA) and contrast sensitivity 9 years postoperatively. Setting : St. Erik Eye Hospital, Stockholm, Sweden. Design : Prospective randomized clinical trial. Methods : One of 3 experienced cataract surgeons performed standard phacoemulsification in 1 eye of each patient. The patients were randomized to implantation of a hydrophobic acrylic IOL or a hydrophilic acrylic IOL. Both IOLs had sharp posterior edges. The CDVA and contrast sensitivity were measured 9 years postoperatively. Scheimpflug images of the IOLs were obtained to analyze glistenings, which were graded subjectively at the slitlamp and quantified objectively with digital image analysis using computer software. Results : Seventy‐eight of the 120 patients were available for the 9‐year follow‐up examination. Patients with the hydrophilic IOL had statistically significantly fewer glistenings ( P < .001). The development of glistenings was not correlated with IOL power, CDVA, or contrast sensitivity. Conclusions : After 9 years, the hydrophobic IOL developed more glistenings than the hydrophilic IOL. Glistenings did not affect CDVA or contrast sensitivity. Financial Disclosure : Neither author has a financial or proprietary interest in any material or method mentioned.